2015
DOI: 10.1037/rep0000037
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychological resilience and mTBI as predictors of postconcussional syndrome symptomatology.

Abstract: The results demonstrate that: (a) both perceived psychological resilience and mTBI history play a role in whether or not PCS symptoms are experienced, even when demographic variables are considered, and (b) of these 2 variables, lower perceived psychological resilience was the strongest predictor of PCS-like symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“… 25 Cross-sectional studies have found that lower levels of resilience are associated with higher symptom-reporting in participants who report having had a mTBI between 1 month and 6 months ago. 27 Similar results have been found in a military veterans sample. 28 However, in a prospective cohort study of emergency department patients, McCauley and colleagues 29 found that higher levels of resilience at baseline (<24 hours) was associated with higher symptom reporting.…”
Section: Introductionsupporting
confidence: 78%
“… 25 Cross-sectional studies have found that lower levels of resilience are associated with higher symptom-reporting in participants who report having had a mTBI between 1 month and 6 months ago. 27 Similar results have been found in a military veterans sample. 28 However, in a prospective cohort study of emergency department patients, McCauley and colleagues 29 found that higher levels of resilience at baseline (<24 hours) was associated with higher symptom reporting.…”
Section: Introductionsupporting
confidence: 78%
“…This relationship, however, might be expected to be negative. Previous studies have observed a negative relationship between illness and psychological resilience [ 4 8 ], although this is normally interpreted as a sign of resilience protecting against the development of illnesses. If those of our participants higher in resilience in older age were already more resilient in childhood, this could have protected against childhood illness and then been retained throughout life into older age.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience has previously been associated with physical and mental health problems [ 4 8 ]. Consistent with such findings, we observed moderate correlations between resilience and health, mental health and wellbeing in older age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent cross‐sectional studies find that self‐reported resilience is associated with adjustment in expected directions among persons with TBI (Losoi, et al., ; Merritt, Lange, & French, ; Sullivan, Edmed, Allan, Smith, & Karlsson, ; see McCauley, et al., , for a more complicated pattern). However, the measures in these studies are limited because they were developed with “no real theoretical model for their concept of resilience, leaving clinicians and researchers with a relatively face‐valid, self‐report measure and little guidance for working with respondents” (Elliott & Erosa, , p. 208).…”
mentioning
confidence: 99%